Peran Teman Sebaya, Orang Tua dan Lingkungan Sekitar Wilayah Lokalisasi Tegal Panas Pada Praktik Pacaran Remaja Awal - Rizsa Fauziah Ichwani; Besar Tirto Husodo; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Early adolescence is the first phase for a child to experience significant changes in the reproductive organs which begin to function optimally between the ages of 12 untill 14 years. This change was also accompanied by changes in the physical to psychological aspects of adolescents. During this time teenagers have begun to experience attraction with the opposite sex. Dating behavior is one of the things that happens in a teenager's life. Tegal Panas is one of the localization areas in Semarang Regency which is located in X village. Around this area there are residents of the teenagers, especially early adolescents. Early adolescents became one of the groups that are vulnerable to being exposed to negative things related to localization that are around the area where they live. The Early adolescence population in X village is 380 people. Determination of the sample in this study used inclusion criteria with a total of 77 respondents. The characteristics of the study respondents were more than 14 years old (41.6%), male sex dominated (53.2%). The chi square test on the independent variable with the dependent variable produces two independent variables related to the dependent variable. pvalue = 0,000 on peer role variables indicates a relationship to the respondent's dating practices. pvalue = 0.043 in the residential environment variable associated with the practice of dating respondents. Age (p value = 0.079), gender (pvalue = 0.553), role of parents at puberty and courtship (pvalue = 0.147) indicates that these values are not related to the practice of courtship of the respondent.